2023
DOI: 10.1101/2023.10.28.562773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attention, Musicality, and Familiarity Shape Cortical Speech Tracking at the Musical Cocktail Party

Jane A. Brown,
Gavin M. Bidelman

Abstract: The cocktail party problem challenges our ability to understand speech in noisy environments, which often include background music. Here, we explored the role of background music in speech-in-noise listening. Participants listened to an audiobook in familiar and unfamiliar music while tracking keywords in either speech or song lyrics. We used EEG to measure neural tracking of the audiobook. When speech was masked by music, the modeled peak latency at 50 ms (P1TRF) was prolonged compared to unmasked. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…Musicians showed increased alpha-band auditory-motor connectivity with training block, whereas nonmusicians did not. In this vein, prior studies have also shown greater selective auditory attention for musicians in concurrent speech or "cocktail party" scenarios (Brown & Bidelman, 2023;Clayton et al, 2016;Strait et al, 2010), but see (Baumann et al, 2008), and there is also evidence that inhibitory attentional control is stronger and more efficient in musically trained individuals (Medina & Barraza, 2019).…”
Section: Musicians Displayed Stronger Modulation Of Alpha Activity Th...mentioning
confidence: 95%
“…Musicians showed increased alpha-band auditory-motor connectivity with training block, whereas nonmusicians did not. In this vein, prior studies have also shown greater selective auditory attention for musicians in concurrent speech or "cocktail party" scenarios (Brown & Bidelman, 2023;Clayton et al, 2016;Strait et al, 2010), but see (Baumann et al, 2008), and there is also evidence that inhibitory attentional control is stronger and more efficient in musically trained individuals (Medina & Barraza, 2019).…”
Section: Musicians Displayed Stronger Modulation Of Alpha Activity Th...mentioning
confidence: 95%